Safety of corticosteroid therapy in sarcoidosis treatment - Di Marco Berardino, Alessandro; Mei, Federico; Zuccatosta, Lina (Frontiers in Drug Safety and Regulation, 2023)
Introduction: Sarcoidosis is a multisystemic granulomatous disease of unknown origin and unpredictable cause, characterized by a dysregulated immune response. If histopathological hallmark is represented by the presence of non-caseating granulomas, clinical manifestations are variable and symptoms are not specific, and they depend on organs affected. Although thoracic involvement (lung and mediastinum) is the most common clinical manifestation, any organ can be virtually affected.Methods: This paper is structured as a narrative review. A literature search was performed in four electronic databases (Pubmed, Cochrane, Scopus, and Ovid Medline) and Google from inception until February 2023 for relevant studies, meta-analyses, and reviews on corticosteroids' adverse events in sarcoidosis. English language only papers were included.Discussion: Although antimetabolites (such as Methotrexate) and immunosuppressant agents can be used as alternative therapy in refractory cases, traditionally systemic glucocorticoids represent the first choice for sarcoidosis treatment. However, their use is still debated, due to potential adverse effects, leading to a wide spectrum of complications particularly in patients who required long-term therapy. Hence, this article aims to provide a comprehensive updated review on the safety profile of glucocorticoid treatment in patients with sarcoidosis and their systemic effects.corticosteroids remain the first choice in Sarcoidosis, however, due to numerous side effects, dose and duration of treatment should be carefully adjusted and monitored by clinicians.